Emotional intimacy, sexual desire, and sexual satisfaction among partnered heterosexual men - Štulhofer, Aleksandar; Ferreira, Luana Cunha; Landripet, Ivan (2014)
In spite of a mostly positive impact of emotional intimacy on sexual desire and satisfaction, emotional merging and the safety and comfort of emotional closeness have been linked with diminished sexual desire. Aiming at a better understanding of the role of intimacy in male sexuality, this paper explored (1) a likely mechanism behind the association between emotional intimacy and sexual satisfaction and (2) whether there is empirical evidence of a negative impact of intimacy on sexual desire. Among 506 heterosexual Croatian men (M = 38.2 years, SD = 8.43) currently living with their partners who participated in a large-scale online survey carried out in 2011, sexual satisfaction was dependent on both intimacy and sexual desire. Emotional intimacy was strongly associated with the partner-centered component of personal sexual satisfaction, pointing to a possible mechanism through which intimacy affects sexual well-being. Despite employing different analytical approaches and controlling for age and the length of intimate relationship, no evidence was found of a negative association between relationship intimacy and male sexual desire. Our study supports the notion that intimacy has an important and positive role in male sexuality